Using Podcast Media to Support Religious Moderation Education: Podcast Analysis Case Log in - Moni Kusuma Wardani; Islah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This study examines the effectiveness of Podcast media in campaigning for religious moderation in Indonesia. This study uses a qualitative method. This study found that through Podcast media, especially Podcasts with the title Log In which is on Youtube channel owned by Deddy Cobuzier, provides an overview of how religious moderation in the midst of various religions in Indonesia. This Podsact has a very big effect on the listeners. The podcast hosted by Habib Ja'far and Onad received positive comments and some of them told the implementation of tolerance in their area.